Summum Bonum - Gomes, Nelson Gonçalves (Analytica - Revista de Filosofia, 2013)
Este artigo apresenta o argumento ontológico de G¶del, intuitiva e formalmente. Duas dentre as suas variações contemporâneas também são apresentadas. O artigo discute as críticas fi losófi cas e teológicas ao argumento. A conclusão à qual se chega é que a correção dos raciocínios de G¶del é um importante resultado lógico que, porém, pede mais trabalho de análise. A idéia metafísica de propriedade positiva (ou de conjunto positivo), por exemplo, carece de clarificação. Abstract This article contains a presentation of G¶del's ontological proof, from both the intuitive and the formal points of view. Two other contemporary variations of it are also presented. The article discusses the philosophical and the theological criticisms of the proof. The conclusion to be drawn is that the soundness of G¶del's reasoning is an important logical result, which nevertheless demands further work of analysis. The metaphysical idea of apositive property (or positive set) for instance needs clarification.